The Impact of Dividend Payout Ratio on Future Earnings Growth: Evidence from Malaysia - Khairul Zharif, Zaharudin (2010)
It is argued that the payout ratio has positive impact on future earnings growth as suggested by Arnott and Asness (2003) and Zhou and Ruland (2006). The aim of this study is to determine the impact of dividend payout ratio on future earnings growth in Malaysia. There was no study in Malaysia that emphasizes on the influence of dividend payout on future earnings growth. The study uses 97 listed companies on Bursa Malaysia as sample, with 485 company-year observations. The regression analysis shows that dividend payout ratio has no impact on future earnings growth. The nature of companies' ownership in Malaysia is the possible explanation for the results.